2000
DOI: 10.1099/00221287-146-9-2105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salivary secretory IgA on the adhesion of Candida albicans to polystyrene

Abstract: Attachment of Candida albicans to plastic materials of dental prostheses or to salivary macromolecules adsorbed on their surface is believed to be a critical event in the development of denture stomatitis. In an earlier study, it was shown that adhesion of C. albicans to polystyrene, a model system to study the adhesion of C. albicans to plastic materials, can be partially inhibited with an mAb directed against cell wall polysaccharides of C. albicans. In the present study, the role of whole saliva in the adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 29 publications
1
38
0
3
Order By: Relevance
“…Furthermore, the adsorption of salivary components can also affect adhesion. It has been reported by several authors that adhesion of Candida albicans to oral surfaces is influenced by saliva [25][26][27][28]. Saliva can enhance the adhesion to acrylic surfaces [27] and polystyrene [28], whereas adhesion to silicone rubber can be discouraged in the presence of saliva [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the adsorption of salivary components can also affect adhesion. It has been reported by several authors that adhesion of Candida albicans to oral surfaces is influenced by saliva [25][26][27][28]. Saliva can enhance the adhesion to acrylic surfaces [27] and polystyrene [28], whereas adhesion to silicone rubber can be discouraged in the presence of saliva [26].…”
Section: Discussionmentioning
confidence: 99%
“…Saliva can enhance the adhesion to acrylic surfaces [27] and polystyrene [28], whereas adhesion to silicone rubber can be discouraged in the presence of saliva [26]. This fact has been attributed to the adsorption of different salivary components, including mucins [29], other salivary proteins [30] and secretory IgA [28].…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al 15 observed that patients with clinical diagnoses of vaginal candidiasis exhibited lower levels of anti-Candida IgA in the saliva. According to San Millán et al, 9 in patients with dental prosthesis or removable orthodontic devices, salivary IgA reduces the adherence of C. albicans to polystyrene. Although the present study did not assess the adhesion of Candida to the surface of the orthodontic device nor the role of IgA in this phenomenon, our results indicate that anti-C. albicans IgA is not the most important factor to determine Candida carrier status.…”
Section: Discussionmentioning
confidence: 99%
“…5 IgA seems to play an important role by causing fungal aggregation and preventing the adherence to mucosa or oral surfaces. 9 Adhesion and colonization of the oral cavity by C. albicans is an initial step in candidosis. The presence of orthodontic and other oral appliances may alter the oral ecological environment.…”
Section: Introductionmentioning
confidence: 99%
“…We have also demonstrated that salivary sIgA inhibits the adhesion of C. albicans to plastic and composite restorative dental materials and that the inhibitory effect can be mimicked by MAbs directed against cell wall antigens of C. albicans (24,36). In this report, we have characterized a monoclonal antibody raised against the main target of salivary sIgA in the cell wall of C. albicans in an attempt to assess whether the monoclonal antibody shows-in addition to the ability to inhibit adhesion of C. albicans to host surfaces-other biological properties such as fungicidal activity, which may be implicated in the protection against mucosal candidiasis.…”
mentioning
confidence: 99%